(untitled) (Research, Society and Development, 2022)
The Encephalic Vascular Accident is a serious disease that affects people in Brazil and worldwide (Soares et al., 2022). This disease is considered a relevant global health problem, with more than 12 million people affected each year, while about 6.5 million of them die (Feigin et al., 2021). Realizing the popularization of cell phones and mobile health applications in Brazil, it is possible to propose innovative apps for education, prevention and self-care in stroke (Soares et al., 2022). The objective of this study was to analyze the scientific production on mHealth mobile health applications for education, treatment and rehabilitation of Encephalic Vascular Accident. Methodology - It is an integrative review, being a research of a basic nature, with a qualitative approach, with an exploratory objective, organized in compliance with the theories of Minayo (Cecília de Souza Minayo & Ferreira Deslandes Otávio Cruz Neto, 2002) and Creswell (Creswell, 2014), which adopted the bibliographic research procedure. Results - A variety of publications were identified in some journals that address mHealth applications for Stroke, which encourages us to realize that the field of applications for stroke presents relevant data that need to be explored, updated and disseminated. Conclusions - Although people express positive perceptions when using mHealth apps for health learning and prevention (Soares et al., 2022), many apps can still be difficult to use (M. F. Alwashmi et al., 2019), due to technical conditions, technologies, age of the user, among other limitations, a situation that can compromise the setting, learning, user experience and perceptions of usefulness of mobile health applications (Nimmolrat et al., 2021), (Morris et al., 2017).